Intervention to Improve Quality of life for African-AmericaN lupus patients (IQAN): study protocol for a randomized controlled trial of a unique a la carte intervention approach to self-management of lupus in African Americans. Issue 1 (December 2016) - Williams, Edith; Lorig, Kate; Glover, Saundra; Kamen, Diane; Back, Sudie; Merchant, Anwar; Zhang, Jiajia; Oates, James
Abstract Background Systemic Lupus Erythematosus (lupus) is a chronic autoimmune disease that can impact any organ system and result in life-threatening complications. African-Americans are at increased risk for morbidity and mortality from lupus. Self-management programs have demonstrated significant improvements in health distress, self-reported global health, and activity limitation among people with lupus. Despite benefits, arthritis self-management education has reached only a limited number of people. Self-selection of program could improve such trends. The aim of the current study is to test a novel intervention to improve quality of life, decrease indicators of depression, and reduce perceived and biological indicators of stress in African-American lupus patients in South Carolina. Methods/Design In a three armed randomized, wait list controlled trial, we will evaluate the effectiveness of a patient-centered 'a–la-carte' approach that offers subjects a variety of modes of interaction from which they can choose as many or few as they wish, compared to a 'set menu' approach and usual care. This unique 'a-la-carte' self-management program will be offered to 50 African-American lupus patients participating in a longitudinal observational web-based SLE Database at the Medical University of South Carolina. Each individualized intervention plan will include 1–4 options, including a mail-delivered arthritis kit, addition and access to an online message board, participation in a support group, and enrollment in a local self-management program. A 'set menu' control group of 50 lupus patients will be offered a standardized chronic disease self-management program only, and a control group of 50 lupus patients will receive usual care. Outcomes will include changes in (a) health behaviors, (b) health status, (c) health care utilization, and (d) biological markers (urinary catecholamines). Discussion Such a culturally sensitive educational intervention which includes self-selection of program components has the potential to improve disparate trends in quality of life, disease activity, depression, and stress among African-American lupus patients, as better outcomes have been documented when participants are able to choose/dictate the content and/or pace of the respective treatment/intervention program. Since there is currently no "gold standard" self-management program specifically for lupus, this project may have a considerable impact on future research and policy decisions. Trial registration NCT01837875 ; April 18, 2013